2018
DOI: 10.11002/kjfp.2018.25.4.461
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced digestive enzyme activity and anti-adipogenic of fermented soy-powder milk with probiotic Lactobacillus plantarum P1201 through an increase in conjugated linoleic acid and isoflavone aglycone content

Abstract: because it is a risk factor or various severe metabolic comorbidities, including diabetes, cardiovascular injury, hyperlipemia and cancer (1,2). Currently, certain anti-obesity drugs are commercially available, including orlistat and sibutramine. Owing to dissatisfaction with the high costs and potentially hazardous side effects, natural products that can regulate adipogenesis have currently received increasing attention and are an excellent alternative strategy to treat obesity (3,4). The use of soybean as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The anti-obesity effect of FSPM can be attributed to conjugated linoleic acid (CLA) and isoflavone aglycones, which downregulated lipoprotein lipase (LPL), adiponectin, adipocyte fatty acid-binding protein (aP2), fatty acid synthase (FAS), and acetyl CoA carboxylase (ACC) mRNA. Additionally, FSPM increased the anti-obesity activity and pancreatic enzymes' inhibitory function [168]. These findings suggest that the fermented hydrolysate milks may have helped to increase the value of the soybean [168].…”
Section: Small Molecule Natural Productsmentioning
confidence: 78%
See 1 more Smart Citation
“…The anti-obesity effect of FSPM can be attributed to conjugated linoleic acid (CLA) and isoflavone aglycones, which downregulated lipoprotein lipase (LPL), adiponectin, adipocyte fatty acid-binding protein (aP2), fatty acid synthase (FAS), and acetyl CoA carboxylase (ACC) mRNA. Additionally, FSPM increased the anti-obesity activity and pancreatic enzymes' inhibitory function [168]. These findings suggest that the fermented hydrolysate milks may have helped to increase the value of the soybean [168].…”
Section: Small Molecule Natural Productsmentioning
confidence: 78%
“…Additionally, FSPM increased the anti-obesity activity and pancreatic enzymes' inhibitory function [168]. These findings suggest that the fermented hydrolysate milks may have helped to increase the value of the soybean [168]. Hwang et al [169] also revealed that in soy-powder yogurts (SPYs) made using Lactobacillus brevis and L. plantarum, the total average isoflavones decreased while there was an increase in aglycones.…”
Section: Small Molecule Natural Productsmentioning
confidence: 93%
“…Soymilk with 2% sucrose was hydrolyzed with 10 U of cellulase, protease, and esterase at 37 °C for 24 h, and finally 1.0% safflower oil and the starter (2.0×10 7 CFU/mL) were added. Fermentation was carried out at 35 °C for 48 h. L. plantarum P1201 increased the content of isoflavones in the aglycone form (daidzein, glycitein and genistein) and produced CLA in fermented soymilk by improving some functional properties that positively influenced adipogenesis and lipid metabolism [118].…”
Section: Cla-producing L Plantarum Strains In Fermented Foodmentioning
confidence: 99%